Peran Kesetaraan Gender dalam Meningkatkan Efektivitas Organisasi dan Mendukung Pencapaian Tujuan Institusional - Rifki Ihza Dermawan; Ririn Handayani; Adolf Bastian (Jurnal Ekonomika Dan Bisnis (JEBS), 2026)
The study was conducted at the Rokan Hulu Police Resort, with the aim of examining the role of job satisfaction in mediating the influence of gender-based HRM practices on performance. The population of this study was 269 people. Based on this population size, using the N population table developed by Krejcie and Morgan namely with N (population) = 269 then n (sample) = 159 samples. The sampling method used in this study is the simple random sampling method. All respondents will be used to obtain primary data related to the variables, which will be collected through a questionnaire with a Likert scale of 1-5 points. All data obtained will be analyzed using Structural Equation Modeling (SEM) with the Smart PLS 3.0 analysis tool. This study found that gender-based HRM practices have a positive effect on performance, gender-based HRM practices have a positive effect on job satisfaction, job satisfaction has a positive effect on performance, and job satisfaction mediates the effect of practices on performance.